Influence of shade and irradiation time on the hardness of composite resins - Della Bona,Álvaro (2007)
This study tested the following hypotheses: 1. increasing light irradiation time (IT) produces greater values of superficial hardness on different depths (0 and 3 mm); and 2. a dark shade composite (A3) needs longer IT than a light shade composite (A1) to produce similar hardness. Disk-shaped specimens (n=24 per shade) were fabricated using a 3-mm-thick increment of composite resin (Z100). Specimens were randomly assigned to 3 groups (n=8) according to the IT (400 mW/cm2) at the upper (U) surface: A1-10 and A3-10: 10 s; A1-20 and A3-20: 20 s; A1-40 and A3-40: 40 s. Specimens were stored in black lightproof containers at 37ºC for 24 h before indentation in a hardness tester. Three Vickers indentations were performed on the U and lower (L) surfaces of each specimen. The indent diagonals were measured and the hardness value calculated. The results were analyzed statistically by ANOVA and Tukey's test (alpha=0.05). Statistically significant differences were found between U and L surfaces of each composite shade-IT combination (p=0.0001) and among the ITs of same shade-surface combination (p=0.0001), except between groups A1-20U and A1-40U, confirming the study hypothesis 1 and partially rejecting the hypothesis 2.